Taperless blade manufacturing using NREL’S 833 air foil on horizontal axis wind turbine - Zulhendrik, Arya; Samuel , Samuel; Jimenez, John Rey A (Researcher and Lecturer Society, 2022)
Wind is an abundant energy source available in nature, which is renewable and environmentally friendly with high work efficiency. Indonesia has a wind potential of 978 MW, with wind speeds ranging from 6-8 m/s in onshore areas to above 8 m/s in offshore areas. Therefore, we should be able to capitalize on this energy resource. This paper will analyze the performance of NREL's 822 taperless type using the Q-Blade application. The research method used begins with a literature study to find natural parameters that will be later calculated using Excel to obtain the geometry parameters of the blades. Then, the data is entered into the Q-blade software by dividing the blades into ten elements and optimizing them. The blade material used in the manufacture is mahogany wood. This paper will discuss the manufacture of taperless blades with NREL's 822 airfoil. The blades were previously designed using MS Excel and Q-Blade applications and then further designed using the Solid Work application.